Enhancing Young EFL Learners’ Oral Communication through Digital Storytelling Strategy Strategy The Case of the Fifth-year Pupils at Tayeb Razouk Primary School in Laghouat - Temmir, Wissam; Korichi, Souhila (Faculty of Letters and Foreign Languages Department of English, 2025)
Digital storytelling (DST) emerges as a powerful pedagogical tool to improve the four language skills, including oral communication. The present study aims to examine the effects of using digital storytelling to enhance oral communication skills among fifth-year primary school pupils at Razouk Tayeb Primary School within the academic year 2024/2025. It was hypothesized that integrating digital stories in young learners’ EFL classrooms could enhance their oral communication skills. To investigate this hypothesis, a quasi-experimental study was conducted involving 29 pupils representing the experimental and control groups. A mixed-methods approach was employed to achieve this aim, utilizing pre- and post-tests in conjunction with classroom observation. The results revealed that digital storytelling helped to improve some elements of oral communication, including fluency, vocabulary, and comprehension, while on the other hand, it did not improve pronunciation and grammar. However, DST helped in promoting young learners’ participation and encouraged them to speak more confidently in the classroom